Inequality in measuring scholarly success: Variation in the h-index within and between disciplines - Ryan Light; Aaron Gullickson; Jill Ann Harrison (PLoS ONE, 2025)
Scholars and university administrators have a vested interest in building equitable valuation systems of academic work for both practical (e.g., resource distribution) and more lofty purposes (e.g., what constitutes “good” research). Well-established inequalities in science pose a difficult challenge to those interested in constructing a parsimonious and fair method for valuation as stratification occurs within academic disciplines, but also between them. The h -index, a popular research metric, has been formally used as one such method of valuation. In this article, we use the case of the h -index to examine how the distribution of research metrics reveal within and between discipline inequalities. Using bibliometric data from 1960-2019 on over 50,000 high performing scientists—the top 2% most frequently cited authors—across 174 disciplines, we construct random effects within-between models predicting the h -index. Results suggest significant within-discipline variation in several forms, specifically sole-authorship and female penalties. Results also show that a sole authorship penalty plays a significant role in well-known between-discipline variation. Field-specific models emphasize the “apples-to-oranges,” or incommensurable, property of cross-discipline comparison with significant heterogeneity in sole-authorship and female penalties within fields. In conclusion, we recommend continued caution when using the h -index or similar metrics for valuation purposes and the prioritization of substantive valuations from disciplinary experts.